Collaborative procurement strategies for infrastructure projects: a multiple-case study. Issue 4 (31st August 2019) - Eriksson, Per Erik; Volker, Leentje; Kadefors, Anna; Lingegård, Sofia; Larsson, Johan; Rosander, Lilly
Abstract : With the announcement to tender a project, several strategic decisions are made that have significant impact on the innovation and efficiency potential of a project. The purpose of this study is to investigate and compare how different types of integrative and collaborative procurement strategies may enhance the opportunities for improved efficiency and innovation in infrastructure projects. Hence, it contributes to the scientific debate on buyer–supplier relationships in relation to project performance. Furthermore, it guides public client organisations in steering explicitly for integration and innovation in their projects. Interview-based case studies of ten public infrastructure projects procured based on four different types of collaborative procurement strategies in Sweden and the Netherlands were conducted. The findings indicate that the duration of the collaboration is fundamental in setting the limits for innovation and that early involvement and long-term commitments in maintenance open up opportunities for more innovation. Naturally, the potential for increased efficiency is higher than for innovation and also occurs in collaborations with limited duration. The findings confirm the importance of a learning perspective on procurement strategies for public client organisations and show the importance of explicit considerations on incentives and project governance issues in the front-end phase of a project.